Pitch Perception in the First Year of Life, a Comparison of Lexical Tones and Musical Pitch - Chen, Ao; Stevens, Catherine J.; Kager, René (Frontiers in Psychology, 2017)
Lexical tones have been considered as phonological contrasts in infant language research. Yet pitch variation pervades in speech, and infants may perceive lexical tones as pitch variations without phonological relevance. We examined whether the development in lexical tone perception may parallel with perception of pitch in other cognitive domains namely music. Using a visual fixation paradigm, one hundred and one 4- and 12-month-old Dutch infants were tested on their discrimination of Chinese rising and dipping lexical tones as well as comparable three-note musical pitch contours. The 4-month-old infants failed to show a discrimination effect in either condition, whereas the 12-month-old infants succeeded in both conditions. These results suggest that lexical tone perception may reflect and relate to general pitch perception abilities, which may serve as a basis for developing more complex language and musical skills.